(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Aims and Obkectives: Left Ventricle of heart, being a muscular organ is capable of undergoing hypertrophy, defined as an increase in the mass of the left ventricle (LVH). LVH can be diagnosed by radiography, echocardiography and electrocardiography. The first two need expertise, not readily available and expensive so the objective is to find out how much we can solely rely on the electrocardiography for the diagnosis of LVH. Study Design: Non probability purpose sampling. Duration: Jan 2012 to Dec 2012 in the cardiology department of Jinnah Hospital Lahore. Results: Majority of the patients between 45-65 years of age 45% (n=90) were found between 56 to 65 years while only 1.5 %( n=3) were found between 16 to 25 years of age. Mean and standard deviation was found on 47.88+4.67. Regarding gender distribution, 67% (n=134) patients were found male and 33% (n=66) were found female. Left ventricular hypertrophy on electrocardiography, 48% (n=96) patients were found positive and 52 %( n=104) were found negative. Conclusion: The frequency of true positive cases of Left Ventricular Hypertrophy on Electrocardiography taking Echocardiography as gold standard is acceptable.